PHYSICAL – MECHANICAL AND TECHNOLOGICAL PROPERTIES OF TIMBER OF THE ORDINARY CHESTNUT FROM DIFFERENT SEEDLINGS IN BULGARIA (Innovation in Woodworking Industry and Engineering design, 2026)
The results from the research on the physical – mechanical and technological properties of the timber of the ordinary chestnut from different seedlings in Bulgaria are announced. Model trees for research have been provided from Belasitsa, Slavyanka, Pirin Mountain and the Western Balkans. It has been found, that the trees of the ordinary chestnut possess suitable decorative – art, physical, mechanical and technological properties for their use in the construction of furniture, doors, windows and the interior components and monuments of culture and national –historical and decorative – art significance. It is recommended to organize a selective timber harvest of the oval chestnut materials and purposeful use of their timber.